Coordination burdened Exercises- condition for the proper development of children - Vuksanovikj, Vladimir; Klincharov, Ilija; Nikovski, Goran; Nedelkovski, Vlatko; Misovski, Andrijana (Faculty of physical education sport and health, 2016)
Choosing the right sports and recreational activities for young age groups is a real challenge. The activities should be adapted to the age, interest, previous experience and abilities of the children that would use them. The coordination as a motor skill is present in every movement. It is directly related to the intellectual abilities. The intellect is needed in order to show the coordination in the movements. Coordination burdened movements are also stimulating the thinking and require consciousness involvement. As an ability, it provides the human the opportunity for self-learning and self-cognition during the learning of the movement and its performance. It is therefore recommended, during the process of creation of activities for the children, to allow them to face the movements they never experienced, that are new for them, but still applicable for their age.
Keywords: coordination; motor skills; development; children; intellect; training